Current opinions regarding the clinical utility of en bloc resection in the treatment of non-muscle invasive bladder cancer—a review of the literature - Wenbo Gao (Discover Oncology)
Abstract Non-muscle invasive bladder cancer (NMIBC) is currently mainly treated with the approach of transurethral resection of bladder tumor (TURBT) followed by pathology investigation of the obtained specimens. However, this approach—TURBT—has a few drawbacks, owing to the inherent technical defect—“piecemeal” resection. With development of medical science and surgical techniques, a new kind of surgical operation—“en bloc” resection of bladder tumor (ERBT)—emerged, hoping to completely remove bladder tumor with surrounding normal tissue. The detrusor muscle layer beneath the tumor is removed, and the surgical quality of bladder tumor is enhanced, with a better pathological outcome, reduced intraoperative complications and lower recurrence rate eventually. This paper reviews current literature concerning a brief history of ERBT developing, surgical steps, its indications, advantages on surgical margin, recurrence during follow-up, pathological performance—presence of detrusor muscle, residual tumor and upstage, as well as such issue as “is reTURBT necessary after ERBT?” and the guiding significance of ERBT in substaging of T1 bladder cancer.